2009
DOI: 10.1111/j.1551-2916.2009.03355.x
|View full text |Cite
|
Sign up to set email alerts
|

High Pyroelectric Properties of Porous Ba0.67Sr0.33TiO3 for Uncooled Infrared Detectors

Abstract: Porous Ba0.67Sr0.33TiO3 (BST) ceramics were fabricated by the solid‐state reaction process, and their micro‐structural, dielectric, and pyroelectric properties were systemically investigated. Compared with dense specimens, porous BST exhibited a higher pyroelectric coefficient (p), a lower dielectric constant (ɛ), and heat capacity (CV), which are beneficial for the development of pyroelectric devices. At room temperature, as the porosity increased from 1.0% to 9.6%, BST ceramics' pyroelectric coefficient incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…For pyroelectric materials, porous ceramics have a lower heat capacity and dielectric constant. It has been reported that both porous PZT and BST materials have a higher figure-of-merit [9][10][11][12]. However, there are still problems with porous PZT pyroelectric materials.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…For pyroelectric materials, porous ceramics have a lower heat capacity and dielectric constant. It has been reported that both porous PZT and BST materials have a higher figure-of-merit [9][10][11][12]. However, there are still problems with porous PZT pyroelectric materials.…”
Section: Introductionmentioning
confidence: 95%
“…(1) indicates that BST does not require to be polarized while being used as a dielectric bolometer; therefore, porous BST is a better candidate for pyroelectric applications. In our previous work, we have fabricated porous BST ceramics with poly (methyl methacrylate) (PMMA), which exhibit good dielectric and pyroelectric properties [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among pyroelectric materials, barium strontium titanate (Ba 1-x Sr x TiO 3 , BST) is intensively studied for several reasons: Sr is an effective solute for decreasing the paraelectricferroelectric phase transition temperature in a wide temperature range [12][13][14][15], leading to enhanced pyroelectric properties around room temperature; BST compositions are environmentally-friendly materials, which might represent viable alternatives to replace Pbbased oxides; the total pyroelectric coefficient can be very large in materials like BST, as shown in previous literature, especially due to the contribution of the induced part [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…And the temperature at which the material displays its largest temperature sensitivity can be matched exactly to devices' ambient temperature simply by changing Ba/Sr ratio [6], which enables the devices for use close at room temperature. The major challenge in designing material systems for pyroelectric devices is the simultaneous requirement of a high pyroelectric coefficient, a low heat capacity, and low dielectric constant and loss [7]. Since material properties are strongly related to the microstructure of materials, fabricating homogeneous and uniform materials is important.…”
Section: Introductionmentioning
confidence: 99%